Studies on The illuminated chronicle - Bak, János M.; Veszprémy, László (Central European medieval texts, 2018)
The present volume of studies is the first Subsidium of the Central European Medieval Text series, accompanying CEMT vol. 9 on the Illuminated Chronicle (formerly called the Vienna Chronicle), written in the fourteenth century, which represents the international artistic style at the royal court of Louis I of Hungary. The volume of the text and its annotations did not allow including the detailed scholarly introduction into the same volume as is the custom with the other CEMT items. The essays in the book analyze the text and the illuminations of the Illuminated Chronicle in literaryhistorical.